2009
DOI: 10.1242/jeb.026997
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of glucocorticoid and mineralocorticoid receptors in pulsatile urea excretion of the gulf toadfish,Opsanus beta

Abstract: SUMMARYGulf toadfish, Opsanus beta, are one among a group of unusual teleosts that excrete urea as their predominant nitrogen end product in response to stressful conditions. Under conditions of crowding or confinement, fasted toadfish excrete the majority of their nitrogen waste in large pulses of urea (>90% of total nitrogen) lasting up to 3 h. An earlier study demonstrated that cortisol has an inhibitory influence on urea pulse size. The present study tested the hypothesis that cortisol mediates changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…Similar to previous studies, crowding resulted in elevated cortisol levels in toadfish compared to toadfish kept in uncrowded conditions (Wood et al, ; McDonald et al, ). Metyrapone treatment was also successful in reducing circulating cortisol levels compared to saline‐injected controls as previously described by Rodela et al, . Also consistent with previous work, the 1 week of crowding experienced by crowded, saline‐treated controls and metyrapone‐treated fish of the present experiment resulted in an increase in plasma urea levels compared to presumably non‐ureotelic, uncrowded fish, likely as a result of an upregulation in urea production via the ornithine‐urea cycle (Walsh et al, ; Hopkins et al, ; Laberge et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to previous studies, crowding resulted in elevated cortisol levels in toadfish compared to toadfish kept in uncrowded conditions (Wood et al, ; McDonald et al, ). Metyrapone treatment was also successful in reducing circulating cortisol levels compared to saline‐injected controls as previously described by Rodela et al, . Also consistent with previous work, the 1 week of crowding experienced by crowded, saline‐treated controls and metyrapone‐treated fish of the present experiment resulted in an increase in plasma urea levels compared to presumably non‐ureotelic, uncrowded fish, likely as a result of an upregulation in urea production via the ornithine‐urea cycle (Walsh et al, ; Hopkins et al, ; Laberge et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the apparent differential effects of stress on [ 3 H]‐ketanserin binding mirrors the relationship that exists in toadfish between cortisol and urea excretion. Specifically, that chronic elevation of cortisol in response to a stressor initiates the upregulation in tUT mRNA expression (McDonald et al, ) as well as upregulates the basolateral membrane recruitment of tUT (Rodela et al, ). However, subsequent elevations in cortisol then inhibit membrane insertion and/or activation of tUT (Wood et al, ; McDonald et al, ; Rodela et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed accumulation of plasma urea likely represented the net influence of enhanced urea production and decreased rates of urea excretion. Previous studies have reported that the amount of urea released during discrete urea pulse events is dependent on the concentration of plasma glucocorticoids; in particular, elevated cortisol inhibits tUT function McDonald et al, 2009;Rodela et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%